Pamulorze, Cebulorze, Grzybki, Rabarbary, czyli o pewnej kategorii przezwisk gwarowych - Kurdyła, Tomasz (Stylistyka, 2024)
The article is dedicated to dialectal nicknames motivated by culinary art. Strictly speaking, they are collective nicknames given to inhabitants of neighbouring villages. Such names are not very well documented in linguistic articles, so they are still waiting for a more comprehensive description. In this article, the motivational characteristics of those onyms, as well as their division and formal description, are presented. The largest group of neighbours’ dialectal nicknames based on culinary art includes anthroponyms originating from the names of dishes characteristic of the nicknamed villages (most of them refer to simple regional dishes or to food which is somehow untypical of a village). The second largest group includes nicknames motivated by activities related to culinary art. Other motivational classes have just an indirect, formal connection with food: these names are based on lexemes related to cuisine, but their motivation is not culinary. They include nicknames motivated by crops characteristic of the nicknamed villages and locative nicknames. A few anthroponyms are individual in nature. All the names were generally created through morphological derivation (derivates with the suffix -arz are dominant). They were rarely created through neo-semantization. The lexemes that were collected and analysed confirm the dynamic nature of nicknaming processes in villages. They constitute a characteristic feature of their language and, at the same time, make an anthroponymic category that is, in a way, universal.